Second-Hand Smoking Prevalence in Vietnamese Population Aged 15 and older: A Systematic Review and Meta-Analysis - Tran Quang Duc; Le Thi Kim Anh; Vu Thi Quynh Chi; Nguyen Thi Thanh Huong; Phan Ngoc Quang (SAGE Publishing, 2022)
Background: Second-hand smoking (SHS) is associated with many health problems. However, its prevalence in the community population aged 15 years and older in Vietnam is unknown. Objectives: To quantify the prevalence of SHS in Vietnamese communities aged 15 and above. Methods: This is a meta-analysis that reviewed studies of the prevalence of SHS in Vietnam published in MEDLINE, Scopus, Pubmed and the WHO library database between 1 January 2010 and 31 December 2019. MedCalc was used to perform all the analyses, and publication bias was determined using funnel plots and Egger regression asymmetry tests. Q-test and I 2 statistic were used to identify heterogeneity across studies. Results: There were 7 articles that met our inclusion criteria 2 surveys at the national level, 3 Cross-sectional studies and 2 Case-control studies) involving 184 921 participants. According to the meta-analysis, the overall random-effects pooled prevalence of SHS was 54.6% (95% CIs: 44.900-64.154) with a high level of heterogeneity ( P  = .0001, Q = 2245.60, I 2  = 99.73%). It is noteworthy that the pooled prevalence of SHS rose throughout the course of the survey years. Our research found no evidence of publication bias. Conclusions: Vietnam has ratified the implementation the WHO Framework Convention on Tobacco Control (FCTC) in 2004, there are still a large number of people who are adversely impacted by SHS. Given the tremendous cost that SHS imposes on health systems, our results underscore the critical need for the Vietnamese government to expedite an implementation of a set of stronger tobacco control practices, thus reducing the incidence of smoking-related illnesses and fatalities.